ISIS in Malaysia: understanding their logics - Maszlee Malik,; Mohd Yazid Zul Kepli, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The threat of terrorism to Malaysia is growing. On June 2016, Malaysia suffered its very first confirmed ISIS-related casualty in a grenade attack on Movida Pub that resulted in the injury of eight people and by 2016, around 300 suspects were arrested and investigated due to allegation of involvement in terrorist activities. From the 261 detainees, 34 (33 Malaysian, and one Indonesian) were charged under SOSMA and sent to Sungai Buloh prison for the remand period while waiting for their sentence. This paper is partly based on a year of interview and observation on the ideological inclination of the detainees. The observation reveals that the belief in the necessity to resurrect a global Islamic State with a Caliph to unite Muslims from all over the world under a single banner has been one of the major motivations for Muslim youths to join ISIS. The paper then proceeds with the uncovering and countering the logic of the Malaysian ISIS-related detainees that the resurrection of a global Islamic State caliphate is the only way to protect the interest of the Muslim community.